HIV prevalence, sexual and HIV testing behaviors among men who have sex with men in the Republic of Cyprus: 2011-2012 data from a cross-sectional study - Pylli, Magdalini (BioMed Central, 2014)
BACKGROUND: The Republic of Cyprus is recognized as a low level HIV epidemic country with strong evidence of an increase in the transmission through the male to male sexual contact. Little is known about the factors that influence the sexual and HIV testing behavior in the Republic of Cyprus. METHODS: This is the first bio-behavioral study among men who have sex with men (MSM) in three major cities in the Republic of Cyprus, conducted between 2011 and 2012. Eligible participants were sampled in gay venues by using time-location sampling. RESULTS: Estimated HIV prevalence was 2.5%. The mean age of the sample was 29 ± 6.6 years old. One out of three MSM has not been tested for HIV in the last year. Multivariate logistic regression analysis revealed that the educational level (AOR 0.23, 95% CI 0.09-0.55), the cocaine use (AOR 3.78, 95% CI 1.21-11.83) as well as the type of sexual partner i.e. steady vs casual (AOR 0.18, 95% 0.08-0.45) were significantly associated with condom use in the last anal intercourse. CONCLUSIONS: HIV prevalence among MSM in the Republic of Cyprus remains low; however more efforts are needed in order to increase HIV awareness and prevent the expansion of HIV epidemic in broader community.